Structural and functional alteration of the gut microbiota in elderly patients with hyperlipidemia - Xia, Meng; Xu, Yafang; Li, Huajun; Huang, Juan; Zhou, Haolin; Gao, Chuanzhou; Han, Jingyi (Frontiers in Cellular and Infection Microbiology, 2024)
Objective To investigate the structure, composition, and functions of the gut microbiota in elderly patients with hyperlipidemia.Methods Sixteen older patients diagnosed with hyperlipidemia (M group) and 10 healthy, age-matched normal volunteers (N group) were included. These groups were further subdivided by sex into the male normal (NM, n = 5), female normal (NF, n = 5), male hyperlipidemia (MM, n = 8), and female hyperlipidemia (MF, n = 8) subgroups. Stool samples were collected for high-throughput sequencing of 16S rRNA genes. Blood samples were collected for clinical biochemical index testing.Results Alpha-and beta-diversity analyses revealed that the structure and composition of the gut microbiota were significantly different between the M and N groups. The relative abundances of Bacteroides, Parabacteroides, Blautia, Peptococcus, and Bifidobacterium were significantly decreased, while those of Lactobacillus, Helicobacter, and Desulfovibrio were significantly higher in the M group. There were also significant sex-related differences in microbial structure between the NM and NF groups, and between the MM and MF groups. Through functional prediction with PICRUSt 2, we observed distinct between-group variations in metabolic pathways associated with the gut microbiota and their impact on the functionality of the nervous system. Pearson's correlation coefficient was used as a distance metric to build co-abundance networks. A hypergeometric test was used to detect taxonomies with significant enrichment in specific clusters. We speculated that modules with Muribaculaceae and Lachnospiraceae as the core microbes play an important ecological role in the intestinal microbiota of the M group. The relative intestinal abundances of Agathobacter and Faecalibacterium in the M group were positively correlated with serum triglyceride and low-density lipoprotein levels, while the relative abundance of Bifidobacterium was negatively correlated with the serum lipoprotein a level.